2020
DOI: 10.3399/bjgpopen20x101031
|View full text |Cite
|
Sign up to set email alerts
|

GP perspectives on hospital discharge letters: an interview and focus group study

Abstract: Background Written discharge communication following inpatient or outpatient clinic discharge is essential for communicating information to the GP, but GPs’ opinions on discharge communication are seldom sought. Patients are sometimes copied into this communication, but the reasons for this variation, and the resultant effects, remain unclear.AimTo explore GP perspectives on how discharge letters can be improved in order to enhance patient outcomes.Design & settingThe study used narrative interviews with 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 54 publications
0
19
0
1
Order By: Relevance
“…The Discharge Communication Study [27] (of which this research is a part) investigated ways of improving the content and processes surrounding discharge letters. Results relating to GP interviews contextualising elements of successful letters [28], and patient interviews (which investigate patient-provider communication) [29] have already been published elsewhere. In this paper we report clinicians' opinions on the quality of discharge letters which are crucial to understanding how to improve inter-professional communication at the time of discharge.…”
Section: Introductionmentioning
confidence: 99%
“…The Discharge Communication Study [27] (of which this research is a part) investigated ways of improving the content and processes surrounding discharge letters. Results relating to GP interviews contextualising elements of successful letters [28], and patient interviews (which investigate patient-provider communication) [29] have already been published elsewhere. In this paper we report clinicians' opinions on the quality of discharge letters which are crucial to understanding how to improve inter-professional communication at the time of discharge.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, several studies from different countries reported that GPs appreciated receiving information on medication changes and reasons in the discharge letter. [33][34][35][36] Our findings show that GPs perceived this as more convenient than having to actively call the-often unavailable or difficult to contact-HPs. Therefore, and not too surprisingly so, the number of GPs contacting HPs after their patients' discharge was low.…”
Section: Gp Levelmentioning
confidence: 69%
“…12 There are also no clear standards for the content, format and manner of feedback delivery appropriate for specific clinical settings, thus feedback may be less effective. 18…”
Section: Barriers To Effective Clinician Feedbackmentioning
confidence: 99%